1984
DOI: 10.1080/00268978400101711
|View full text |Cite
|
Sign up to set email alerts
|

An effective pair potential for dipolar fluids

Abstract: The possibility of representing the orientational correlations in a dipolar fluid by an effective pair potential, Ueff(r), depending only on the separation r, is considered. Uetf(r) is obtained from the two-particle orientational partition function by series expansion and direct numerical integration methods for a wide range of interaction strengths. Free energies are obtained for the dipolar hard sphere fluid by use of the GvdW theory of simple fluids and compared with Monte Carlo simulation results. The coex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Even the simpler model of dipolar fluids (the dipolar hard-sphere system) shows a quite complex behaviour. By averaging over the orientations the dipolar interaction a Lennard-Jones-like effective potential is obtained [4,5], so it was conjectured that the dipolar hard-sphere would have a gas-liquid phase transition similar to the observed in simple fluids. However the seminal N V T computer simulation study by Weis and Levesque [6,7] showed no indication of a liquid-vapour transition.…”
mentioning
confidence: 99%
“…Even the simpler model of dipolar fluids (the dipolar hard-sphere system) shows a quite complex behaviour. By averaging over the orientations the dipolar interaction a Lennard-Jones-like effective potential is obtained [4,5], so it was conjectured that the dipolar hard-sphere would have a gas-liquid phase transition similar to the observed in simple fluids. However the seminal N V T computer simulation study by Weis and Levesque [6,7] showed no indication of a liquid-vapour transition.…”
mentioning
confidence: 99%
“…11,67 From a computational point of view, short-range many-body interactions could be easier to treat than long-range two-body interactions, in some situations. To this end, the two-body interaction potential can be developed in a number of ways beyond the leadingorder term used in this work, [33][34][35][36][37][38][39][40]45 and the three-body Axilrod-Teller potential can be retained as the chain-forming interaction. The prospect of moving to four-body interactions is not appealing.…”
Section: Discussionmentioning
confidence: 99%
“…Many attempts have been made to determine an effective two-body potential by taking angular averages of the Boltzmann distribution. [33][34][35][36][37][38][39][40] If the RDF is available, 41 then one can seek a unique density-dependent effective pair potential 42 by using iterative Boltzmann inversion starting from the potential of mean force −k B T ln g(r), 43,44 or by inverting the Ornstein-Zernike equation. 45 A different approach is taken here, based on a model system with two-body −r −6 attractions and three-body AT interactions -with the aforementioned temperature-dependent coefficientscomplemented by a soft-sphere repulsion.…”
Section: Introductionmentioning
confidence: 99%
“…This adds significant complication to the surface tension problem. Following a series of earlier studies stretching from Keesom and Rushbroke through to more recent work by Woodward and Nordholm, , we shall use an effective potential method to map the dipole−dipole interaction onto an equivalent spherically symmetric form. Using a Stockmayer form for the pairwise interaction in the polar fluid, we then arrive, as discussed in an earlier note, at a modified Lennard-Jones potential where the parameters have become temperature dependent.…”
Section: Introductionmentioning
confidence: 99%